The Impact of Leadership Styles on the New Generation Employee Turnover Intentions - Huang, Peixuan (2020)
The new generation of employees is the mainstay of today's workforce, sharing different values and personality traits than baby boomers and Gen X employees, and the turnover rate of the new generation is significantly higher than that of the two generations. Frequent employee turnover can seriously affect the stability and growth of an organization; therefore, it is necessary for contemporary organizations to explore and adopt appropriate methods to curb their turnover intention. Hence, from the perspective of leadership style, this study will adopt the method of quantitative research to collect and analyse the data of the new generation of Chinese employees and compare with the results of previous studies. The results show that benevolent and moral leadership in paternalistic leadership style can significantly inhibit the turnover intention of new generation employees; in contrast, authoritative leadership can promote their turnover intention. In addition, inclusive leadership style can also better help organizations to retain new generation employees. At the same time, some demographic variables will also have some differential impact on leadership styles and turnover tendencies.